PENGARUH PENGENDALIAN INTERNAL DAN KOMITE AUDIT TERHADAP PENCEGAHAN FRAUD PADA PT TDC KISEL DI KABUPATEN OGAN ILIR - Kusminaini Armin (Universitas Tridinanti, 2019)
This study aims to examine the Effect of Internal Control and Audit Committee on Fraud Prevention at PT TDC KISEL in Ogan Ilir Regency. In this study the authors used data analysis techniques namely qualitative data and quantitative data. To collect data from this study, the Survey Questionnaire was used by selecting the sample using the Random Sampling method. Based on the results of the calculation of the F test for the two independent variables Internal Control (X1), and the Audit Committee (X2) obtained a significant value of the dependent variable Prevention of Fraud (Y), namely the Fcount is greater than the Ftable (4.302> 3.260). Then the results of t-arithmetic shows that of the two independent variables namely Internal Control (X1) with a t-test value of 2,279 for the Audit committe (X2) is 1,792 this proves a significant effect on fraud prevention with a significant level of 0.05. KISEL must always detect fraud through prevention, by improving internal control systems, such as the control environment, risk assessment, information and communication systems, control and monitoring activities, and the audit committee must carry out its duties and responsibilities in accordance with applicable regulations. Keywords: Influence of Internal Control, Audit Committee and Fraud Prevention.